Sharon Smith : freelance writer. - Smith, Sharon M. (Brisbane : Sharon Smith, 2010)
"Editor, freelance journalist, digital publishing strategist and writer of fiction."--About.
Title from title screen (viewed on 2 July 2015)
Mode of access: Available online. Address as at 02/07/15
Selected for archiving
Keywords: Authorship; Australian